Theology and Creed in Sunni Islam - Halverson, J. author. aut Link
VII, 188 p.
Keywords: This book explores the correlation between anti-theological thought and the rise of Islamism in the twentieth century by examining Egypt's Muslim Brotherhood and the leadership of Umar al-Tilmisani (d. 1986).